6-Mercaptopurine and Inflammatory Bowel Disease: Hidden Ground for the Cytomegalovirus. (1st May 2003) - Hookey, LC; Depew, W; Boag, A; Vanner, S
Abstract : 6-Mercaptopurine (6-MP) and azathioprine are important drugs for the treatment of inflammatory bowel disease (IBD) but their actions suppress host defense against infection. A challenging case of a 19-year-old female patient with quiescent Crohn's disease maintained with 6-MP presenting with dyspnea and a normal chest exam and x-ray is presented. She became ventilator-dependent and only after numerous investigations was diagnosed with cytomegalovirus (CMV) pneumonitis. A systematic literature review of CMV infections in IBD patients was performed. The present case is the first report of a patient with quiescent IBD maintained on 6-MP who developed CMV pneumonitis. Other reports have identified patients with active disease on multiple immunosuppressants who developed CMV pneumonitis and also highlight the risk of CMV colitis in refractory IBD. The authors review the approach to the diagnosis of CMV infections in IBD patients with atypical pneumonia and colitis and highlight the importance of considering CMV infection in these settings.